Analysis of the clinical outcomes of fetal bowel dilatation combined with other abnormal ultrasonographic features. (19th March 2019) - Xu, Suting; Zhong, Wei; Shen, Zhuanxing; Dai, Changping; Xia, Huimin; Guan, Qiansi; Bai, Lihua; Yu, Jiakang
Abstract: Objectives: To explore the significance of fetal bowel dilatation combined with other abnormal ultrasound features in the diagnosis of gastrointestinal malformation. Methods: A retrospective study of fetuses with bowel dilatation was performed, from August 2012 to October 2015. All the cases were identified from the ultrasound database and all observations of the relationship of prenatal abnormal abdominal ultrasound features and intestinal malformation were performed through the infancy stage. Results: We found 52 fetuses with prenatal suspicion of bowel dilatation. Of these, 20 cases were surgically confirmed to have intestinal malformation, 13 cases had no abnormal bowel loops after birth, 8 cases had abnormal intestinal features while no surgical intervention was performed after birth, 10 cases were lost to follow-up and 1 fetus died in utero at 34 weeks of gestation. Forty cases with full data were divided into three groups, including Group A (Small bowel dilatation combined with other features vs. Isolated small bowel dilatation), Group B (Colonic bowel dilatation combined with other features vs. Isolated colonic bowel dilatation) and Group C (Bowel dilatation combined with other features vs. Isolated bowel dilatation). The intestinal malformation occurrence rates were 73.33% vs. 31.25% in Group A, 50% vs. 25% in Group B, and 70% vs. 30% in Group C. These results suggest that malformation occurs at a lesser frequency in simple bowel dilatation versus bowel dilatation in combination with other abnormal ultrasound features ( p = .026), similarly in simple small bowel dilatation versus small bowel dilatation in combination with other abnormal ultrasound features ( p = .032). Conclusions: Prenatal bowel dilatation in combination with other abnormal ultrasound features, especially small bowel dilatation in combination with other abnormal ultrasound features, detected in the second and third trimesters, tended to indicate intestinal malformation, which contributes to enhance the accuracy of prenatal diagnosis of intestinal malformation.